Strategi Branding Pemasaran UMKM Batik LAZARUS Jember dalam Mempertahankan Eksistensi Pasar Lokal - Supangat, Alfian; Kamila, Siti Nur; Ulhaq, Fahim Dhiya; Aziz, Abd. Rijalul; Silvia, Silvia; Farkhansa, Sulthon; Muzayyanah, Titik; Rizal, M. Saiful; Wulandari, Ria; Pribadi, Adhelia Nanda; Muzayyin, Muzayyin (Journal of Health, Education, Economics, Science, and Technology, 2025)
This research aims to examine the branding strategy implemented by UMKM Batik LAZARUS Jember in maintaining its existence in the local market. This research approach is descriptive qualitative with data collection techniques through observation, in-depth interviews and documentation. Informants were selected purposively, including MSME owners, employees and regular customers. Data analysis uses the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The research results show that the branding strategy used includes visual consistency of brand identity, collaboration with local influencers, and active participation in community events. This strategy has been proven to increase brand awareness and consumer loyalty, as well as strengthen the position of MSMEs in the increasingly competitive local market.